Ecopolitical discourse: Authoritarianism or democracy? - Evidence from China. - Xinyun Hu; Mingming Li (PLoS ONE)
From the discourse analysis perspective, ecopolitics has experienced a discourse change from authoritarianism to democracy. This study uses theory of authoritarianism and democracy in ecopolitics to explore the impact of authoritarian ecopolitical discourse (AED) and democratic ecopolitical discourse (DED) on environmental quality in China. After analysis using panel data and comparison of three main regions, results suggest a negative relationship between AED of the central government and environmental quality. By contrast, a positive relationship exists between AED of local governments and environmental quality. A positive relationship exists between DED, which measures the proposals of People's Congress deputies and Chinese People's Political Consultative Conference (CPPCC), and environmental quality. Nevertheless, the positive effect of DED is weaker than that of AED. The impact is also different among the regions. Our interpretations are as follows. China's current governance mechanism is a top-down decision-making mechanism, rather than a bottom-up information transmission mechanism. The concentration of power keeps decision-making power and resources away from levels with considerably accurate information and capabilities in problem solving. Therefore, we suggest that governments should change their decision-making process and exert effort to be transparent to the entire society. A bottom-up mechanism of information collection and transmission should be established, such as environmental inspection mechanism and checking on cadres' achievements with green GDP.